The mature larva and pupa of Tychius subsulcatus Tournier, 1847 (Coleoptera, Curculionidae), with comments on its biology and phylogenetic relationships - Báborská, Zuzana; Skuhrovec, Jiří; Košťál, Michael (Zootaxa, 2019)
The larva and the pupa of the Palaearctic weevil species Tychius subsulcatus Tournier, 1847 are described and illustrated for the first time. The characters of larva and pupa of T. subsulcatus completely fit the described differential diagnosis of the subtribe Tychiina, genus Tychius, and also Tychius intrusus group. Astragalus onobrychis Linnaeus is confirmed as its host plant. The biology of T. subsulcatus in south Slovakia (Cerová vrchovina Mts.) is described.